VD_FINDINFO HC / 2011 / 630 vom 25. Oktober 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, RÉSILIATION ABUSIVE, INSUBORDINATION, OPPOSITIONPROCÉDURE | 8 CC, 335 al. 1 CO, 336 al. 1 let. a CO, 336b CO, 308 al. 1 CPC